Lung Ultrasound as a Tool to Evaluate Fluid Accumulation in Dialysis Patients - Maria-Eleni Alexandrou; Marieta P. Theodorakopoulou; Pantelis A. Sarafidis (Karger Publishers, 2022)
Background: Volume overload is the main mechanism of BP elevation in end-stage kidney disease (ESKD) patients undergoing hemodialysis or peritoneal dialysis and has been linked to adverse outcomes and increased mortality in this population. Summary: This review discusses current knowledge on lung ultrasound as a tool for detection of extracellular volume overload through evaluation of extravascular lung water content. We describe the principles of lung US, the main protocols to apply it in clinical practice, and accumulated data evidence regarding its associations with cardiovascular events and mortality. We also summarize available evidence on the effect of lung ultrasound-guided volume management strategies on BP control, echocardiographic parameters, and major outcomes in patients undergoing dialysis. Key Messages: Among interventions attempting to reduce the burden of cardiovascular disease in ESKD, effective management of volume overload represents an unmet clinical need. Assessment of hydration status by lung ultrasound is a cheap, easy to employ, and real-time technique that can offer accurate dry weight assessment leading to several clinical benefits.